In Vivo Antimalarial Evaluation of Crude Extract, Solvent Fractions, and TLC-Isolated Compounds from Olea europaea Linn subsp. cuspidata (Oleaceae). (14th May 2020) - Hailesilase, Gebretekle Gebremichael; Rajeshwar, Yarra; Hailu, Gebremedhin Solomon; Sibhat, Gereziher Gebremedhin; Bitew, Helen
Abstract : Malaria is a major global public health problem caused by Plasmodium parasites. Drug resistance is becoming a great challenge. New drugs with novel mechanism of action are urgently required. In malarious countries, medicinal plants are commonly used for malaria treatment. Olea europaea is traditionally used against malaria in Ethiopia. The aim of this study was to isolate and evaluate antimalarial activity of chemical constituents extracted from Olea europaea against chloroquine-sensitive Plasmodium berghei -infected mice. Stem bark of Olea europaea was extracted with 80% methanol and fractionated with three solvents. The butanol fraction was subjected to isolation with preparative thin-layer chromatography (PTLC). Acute oral toxicity studies were conducted in mice as per the Organization for Economic Co-operation and Development (OECD) guideline 425. Antimalarial activities of the test substances were evaluated using Peter's 4-day suppressive test. The crude extract showed significant (p < 0.01 ) antiplasmodial activity at all doses with a chemosuppression value of 52.40% at a dose of 600 mg/kg. All fractions also suppressed parasitaemia significantly (p < 0.05 ), the highest suppression (45.42%) being with butanol fraction. In the phytochemical analysis, two compounds were isolated. Both compounds showed significant (p < 0.05 ) antimalarial activities. Compound C inhibited parasitaemia up to 38.19% at a dose of 200 mg/kg. The crude extract, butanol fraction, and isolated compounds also prolonged survival time of mice. No sign of toxicity and mortality was seen in the test substances at up to a single dose of 2 g/kg. Findings of the current study may confirm the traditional antimalarial claim of Olea europaea and its relative safety as well as the potentiality of compound C for further investigations.